The Effect of Selenium Biofortification on The Growth and Biochemical Responses of Two Microgreen Species - Nosa Finalia; Karno Karno; Rosyida Rosyida (Jurnal Ilmu Pertanian Indonesia, 2026)
Microgreens are a type of vegetable crop that may be grown at a young age (7−14 days) and have a high nutritional value. Microgreens from the Brassicaceae family, such as red radish and broccoli, contain a variety of antioxidants. Selenium biofortification improves microgreen quality and selenium content. The purpose of this study was to determine the influence of selenium levels and the differences between microgreen species. This study was carried out in November−December 2023 at a housing development on Kudan Street in Semarang City, Central Java. Chlorophyll and carotenoid analyses were performed at the Plant Physiology and Breeding Laboratory, Faculty of Animal and Agricultural Sciences, the Waste Treatment Laboratory at the Faculty of Engineering conducted the phenol analysis, while the Cendekia Nanotech Hutama Chemical and Biological Analysis Laboratory in Semarang City performed the antioxidant analysis. This study utilized a randomized complete block design with a factorial pattern of 5×2 and four replications. The first factor was selenium concentration, which had five levels: 0, 2, 4, 6, and 8 mg/L. The second factor was microgreen species, which consisted of two components: red radish and broccoli microgreens. The study found that treating broccoli microgreen with selenium at a concentration of 4 mg/L increased total chlorophyll content and antioxidant capability. Broccoli outperformed red radish microgreens on all metrics. Keywords: antioxidant, biofortification, microgreens, weight, selenium